Social stratification and political articulation: Why attitudinal class differences vary across countries - Staffan Kumlin; Stefan Svallfors (Luxembourg Income Study (LIS), 2008)
Class differences in attitudes towards redistribution are compared across European countries. Two main competing hypotheses are tested, using scatterplots and multi-level modelling. The first is that class differences in attitudes are affected mainly by real class stratification, so that class differences tend to be larger where class differences in incomes and living standards are larger. The second is that such attitudes are affected mainly by class articulation and organisation; that is, the articulation of class issues in political programs and debates and trade union density. The analysis builds on data from the 2002 round of the European Social Survey, data from the Luxembourg Income Study and from the Comparative Manifesto Data Set. Results show that both stronger unions and more attention to class issues by parties independently strengthen the class-attitude link. Large income differences are instead typically associated with small class variance in attitudes: class differences in attitudes tend to be larger in countries with little inequality. The negative correlation between the degree of inequality and the strength of the class-attitudes link persists even after controlling for various measures of political articulation.
Keywords: 330; Einkommensverteilung; Einkommensumverteilung; Lebensstandard; Soziale Schicht; OECD-Staaten